1975
DOI: 10.1042/bj1510699
|View full text |Cite
|
Sign up to set email alerts
|

Purification of the Thy-1 molecule from rat brain

Abstract: The present paper describes the characterization of the Thy-i molecule from rat brain. The molecule was recognized by its antigens, which could be solubilized from brain membrane with deoxycholate. In the solubilized form the Thy-i antigens were associatQd with a homogeneous component with the following hydrodynamic properties: s2O,W= 2.2S, v = 0.72ml/g and Stokes radius = 3.0nm. The mol.wt. of the deoxycholateantigen complex was estimated to be 27000; these values are not significantly different from those ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(47 citation statements)
references
References 28 publications
7
40
0
Order By: Relevance
“…3B). Since Thy-1 is Ͼ10-fold more abundant than PrP (assessed by the degree of purification required from brain; (42)(43)(44)), the lipids associated with 20% of PrP present in the Thy-1 DRMs would be a minor contaminant when compared with those associated with the more abundant Thy-1.…”
Section: Separation Of Prp and Thy-1 On The Membrane And Inmentioning
confidence: 99%
“…3B). Since Thy-1 is Ͼ10-fold more abundant than PrP (assessed by the degree of purification required from brain; (42)(43)(44)), the lipids associated with 20% of PrP present in the Thy-1 DRMs would be a minor contaminant when compared with those associated with the more abundant Thy-1.…”
Section: Separation Of Prp and Thy-1 On The Membrane And Inmentioning
confidence: 99%
“…Thy-i antigen and construction ofinhibition assays 125I-labelled antibody was incubated with thymocyte Thy-i antigen purified as described by LetarteMuirhead et al (1975) or with brain Thy-i antigen as described by Barclay et al (1975), with the modification that lipid was removed by chloroform/ methanol (2: 1, v/v) extraction and that an affinity column of MRC OX 7 monoclonal antibody was used rather than lectin affinity chromatography (A. F. Williams, unpublished work). The pure Thy-i antigen was precipitated with ethanol to remove deoxycholate and solubilized in 3mM-NaN3.…”
Section: Measurement Of Rate Of Dissociation With Solublementioning
confidence: 99%
“…The antigenic specificity for Thy-1 isolated from both nervous and lymphoid tissue ap pears to reside in a glycoprotein of approxi-mately 25,000 daltons [5,23,24,46]. Although the amino acid composition of Thy-1 from brain and thymus appears to be the same, Williams et al [43] have found substantial dif ferences in their carbohydrate compositions.…”
Section: Introductionmentioning
confidence: 99%